The transmembrane protein Syndecan is required for stem cell survival and maintenance of their nuclear properties. - Buffy L Eldridge-Thomas; Jerome G Bohere; Chantal Roubinet; Alexandre Barthelemy; Tamsin J Samuels; Felipe Karam Teixeira; Golnar Kolahgar (PLoS Genetics)
Tissue maintenance is underpinned by resident stem cells whose activity is modulated by microenvironmental cues. Using Drosophila as a simple model to identify regulators of stem cell behaviour and survival in vivo, we have identified novel connections between the conserved transmembrane proteoglycan Syndecan, nuclear properties and stem cell function. In the Drosophila midgut, Syndecan depletion in intestinal stem cells results in their loss from the tissue, impairing tissue renewal. At the cellular level, Syndecan depletion alters cell and nuclear shape, and causes nuclear lamina invaginations and DNA damage. In a second tissue, the developing Drosophila brain, live imaging revealed that Syndecan depletion in neural stem cells results in nuclear envelope remodelling defects which arise upon cell division. Our findings reveal a new role for Syndecan in the maintenance of nuclear properties in diverse stem cell types.